The global bifurcation of agriculture - von Braun, Joachim (2004)
Early economic theory suggested that economic growth associated with the globalisation of agriculture would lead to more equal distribution of income and resources. However at the start of the 21st century it is apparent that the opposite is happening: agriculture is becoming increasingly divided both globally and within many countries, undermining long term growth and fostering political conflict.